UNESCO World Heritage List and Transboundary Serial Heritage Concept: The Potential of Turkey - Akcabozan Taskiran, Aylin; Binan, Can S. (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2020)
World Heritage nominations that extend beyond the borders of one or more countries are defined as transboundary heritage sites. By the emergence of the concept of Transboundary Heritage, UNESCO World Heritage List has started to address more universal nominations with the outstanding universal value, as well as beyond the borders of countries. This new process includes identifying, developing, presenting and preserving the common heritage of the countries through international cooperation. The aim of this study is to determine the basic principles for the identification, presentation, development and protection of transnational serial heritage sites at international, regional and national levels and to propose an evaluation model for potential transboundary or transnational serial heritage proposals. The scope of this paper is to examine Transnational Serial Heritage concept and putting forward the potential of Turkey's common heritage. The research argues the necessity of a new definition for Outstanding Universal Value and new criteria which are needed for the identification and evaluation of transboundary heritage sites. The study further aims to demonstrate Turkey's serial heritage potential through cooperation projects by the States Parties. In this context, three related topics have been discussed. The article begins with an examination of the terminology related to transboundary and transnational serial heritage. Then, a number of examples of transnational serial cultural assets, which are included in the World Heritage List, are evaluated. Secondly, the reasons, strengths, challenges and potentials of this new trend of the UNESCO World Heritage System are discussed. By analyzing the World Heritage List and Tentative List of Turkey and its neighbours, transnational serial nomination concept is evaluated through similar cultural assets and sites. Finally, as a synthesis, the results of the identification, development and protection of the transnational serial heritage are discussed.
Keywords: Shared heritage; transnational serial heritage; Turkey's potential; transboundary heritage; UNESCO World Heritage; Architecture